Early Childhood in Postcolonial Australia Children's Contested Identities - Srinivasan, Prasanna; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
Early Childhood in Postcolonial Australia is a critical narration of how Australian children use cultural markers such as, skin color, diet and religious practices to build their identity categories of'self' and'other.'.
Keywords: Education; Philosophy and social sciences; International education; Comparative education; Educational policy; ducation and state; Educational sociology; Education -- History; Sociology; Education and sociology; Sociology, Educational; Education; History of Education; International and Comparative Education; Sociology of Education; Sociology, general; Educational Policy and Politics; Philosophy of Education